Manajemen Dakwah Masjid Nur Hikmah dalam Meningkatkan Partisipasi Gen Z untuk Memakmurkan Masjid - Abdullah Habib Nasution; Tengku Walisyah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
Mosques play a strategic role as centers for worship, education, and community empowerment; however, low participation from Generation Z (Gen Z) posesa challenge to efforts aimed at revitalizing mosque activities. This study aims to analyzethe implementation of dakwah (Islamic outreach) management at the Nur Hikmah Mosque in an effort to increase Gen Z engagement. A qualitative method with a descriptive approach was employed, utilizing observation, interviews, and documentation involving the Mosque Prosperity Council (BKM) administrators, mosque youth groups, and community leaders. The results indicate that applying dakwah management functions specifically planning, organizing, implementation, and supervision successfully fosters increased Gen Z participation. Program planning takes into account the characteristics of the digital generation; organizing is conducted participatively by involving Gen Z inthe management structure; and dakwah activities are packaged in creative, communicative, and digital-based formats. Supervision is carried out through continuous evaluation to ensure program effectiveness. Supporting factors include open leadership, an inclusive mosque environment, and the utilization of digital technology, while inhibiting factors include a lack of communication and the negative influence of the digital environment. The implementation of adaptive and innovative dakwah management renders the mosque more relevant to the younger generation and contributes to the moral and social development of the community.